Planning optimal library spaces principles, processes, and practices - Moore, David R. II 1966-; Shoaf, Eric C. (Rowman & Littlefield, 2018)
This book demystifies library space planning, inspires creative thinking, and offers immediate how-to steps to seemingly hopeless situations. Including case studies and printed in full color with 148 images, this is a must-have book for librarians, architects, and government/education administrators who work with library building projects"-- Provided by publisher.